Your Emergency Survival Handbook - Paloma (Mandaluyong City, Philippines : Anvil Publishing, 2011)
A must-have for every member of the family, this handbook covers about all there is to know in preparing and surviving every imaginable emergency scenario and more. Advertising guru and chair of the Cultural Center of the Philippines Emily Abrera, "I found the handbook stock full of valuable tips, like how to maximize the use of goods you tend to accumulate in your pantry, ways to disinfect water, and what Chinese concoctions to store in your first-aid kit."
Keywords: Emergency management; Disaster relief